Mexico : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper on Mexico presents econometric investigation of the cyclical determinants of remittances to Mexico. The aggregate U.S. business cycle is not necessarily relevant for remittances. Remittances to Mexico do show a significant relationship with employment conditions in certain regions of the United States. Employment conditions in the U.S. construction sector seem to be especially important as well as remittances for certain regions of Mexico with high rates of emigration, and for many low-income households where they may constitute a sizable share of total income.